THE TASK OF SYNTHESIS OF INDIVIDUAL CURRICULUMS IN THE SPACE OF VIRTUAL LEARNING GROUPS - Christina A. Denks; Yury Yu. Yakunin; Darya I. Yareshchenko (Статистика и экономика, 2016)
The approach of educational planning and organization of educational process is offered to provide students the ability to select and adjust trajectories of learning. The mathematical description of curriculum and algorithm of synthesis individual curriculums are presented. The results of applying the algorithm are showed using an automated system.